An Analysis and Development of Recycled Materials for Wood Plastic Composite Product - Sihombing, Haeryip; Rassiah, Kannan; Ashaari, Zaini; M.Y., Yuhazri (2012)
This study is to find out the best optimum ratio of the mixed waste materials of high-density polyethylene and wood’s flour by comparing the mechanical properties of recycled product (WPC). In this study, the fabrication process of wood plastic composite (WPC) contained of virgin material, post-consumer high-density polyethylene, and wood’s flour is through a twin-screw extruder and hot compression machine. The WPC product with four different ratio filler content based on weight percentage, i.e. 0 wt %, 20 wt %, 30 wt % and 40 wt % , were tested using universal tensile machine and impact tester according to ASTM D 3039, ASTM D 790, and ASTM D 6110 . The results of experiment showed that tensile and flexural properties of the composite increased with the adding of the wood’s flour material. The testing showed, however, totally opposite to the result of the impact test. In overall, the results of observations showed that recycled WPC have better mechanical properties compared to non-recycled WPC.